2009
DOI: 10.1007/s11200-009-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-related gravity field changes at Beijing-Tangshan gravimetric network during 1987–1998

Abstract: Based on the 46 batch repeated observations of Beijing-Tangshan gravimetric network, the gravity field changes of the region during 1987−1998 have been determined. A comparison was made between the differences of these gravity field changes and the 8 reasonably large earthquake events (M b ≥ 4.0) in the region, showing the existence of the earthquake-related gravity field changes. It appears that there is usually a detectable change of a nearby gravity field well before an earthquake, followed by an opposite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…Additionally, as the relation between earthquake and the timing of a detected LGFC, it is still too early to draw any conclusion. The facts reported in the paper should be considered as some new evidence supplemented to those already reported in the past (Li et al, 2009;Li et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, as the relation between earthquake and the timing of a detected LGFC, it is still too early to draw any conclusion. The facts reported in the paper should be considered as some new evidence supplemented to those already reported in the past (Li et al, 2009;Li et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…From these 46 batch results, relative change of gravity field during the time of any two observational epochs can be derived with which the existence of a LGFC, being related to an underground mass migration, is checked. Quite the same as reported (Li et al, 2009), the LGFCs found are usually in pair, having almost the same shape and size but opposite in sign, and usually related to the timing of an earthquake in the area (Li et al, 2009;Li et al, 2011). Figure 3 shows two pairs of them: the LGFC(1)-LGFC(2) and the LGFC(3)-LGFC(4), of which the correlation coefficients are -0.67 and -0.89 respectively.…”
Section: Bttz Gravimetric Network and The Local Gravity Field Changesupporting
confidence: 67%
“…Tangshan is a place where earthquakes happen frequently (Figure 1). The PLV, obtained by gravimetry technique, is shown in Figure 2, in which an annual term is also found [3] The PLV time series is very close to its regression straight line, thus its component on the line is considered as a main one with which a comparison is made with the earthquakes around. It appears that earthquakes (M > 4.0) usually happen near the time when the PLV begins its opposite moving (Figure 3) [3,4].…”
Section: Plv At Tangshan and Its Relation To The Earthquakes Around (mentioning
confidence: 79%
“…Their results further showed the variations of the horizontal component (plumb line) of gravity field existed before earthquake, and the variations of horizontal component are the variations of plumb line. The anomalous variation of the plumb line may be a valuable premonitory phenomenon before earthquake [30]. In 1991, commission 19th (Rotation of the Earth) of IAU hoped Shanghai Astronomical Observatory can continue to collect these data in order to investigate the possibility of getting the long period variations of the plumb line.…”
Section: Significance and Research Progress Of Atlr Anomalies Before mentioning
confidence: 99%